2006
DOI: 10.1021/jf052937v
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Furan and Methylfuran Formed in Different Precursor Systems by Proton Transfer Reaction Mass Spectrometry

Abstract: Furan has recently received attention as a possibly hazardous compound occurring in certain thermally processed foods. Previous model studies have revealed three main precursor systems producing furan upon thermal treatment, i.e., ascorbic acid, Maillard precursors, and polyunsaturated lipids. We employed proton transfer reaction mass spectrometry (PTR-MS) as an on-line monitoring technique to study furan formation. Unambiguous identification and quantitation in the headspace was achieved by PTR-MS/gas chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(102 citation statements)
references
References 25 publications
4
96
1
1
Order By: Relevance
“…Only recently, Märk et al (2006) studied furan formation using three main furan precursors, i.e. ascorbic acid, Maillard precursors, and polyunsaturated lipids.…”
Section: Analysis Of Furan In Foodmentioning
confidence: 99%
“…Only recently, Märk et al (2006) studied furan formation using three main furan precursors, i.e. ascorbic acid, Maillard precursors, and polyunsaturated lipids.…”
Section: Analysis Of Furan In Foodmentioning
confidence: 99%
“…Relative peak area (%) = Peak area of total hydrocarbons/ Total peak area of volatile compounds x 100. In general, hydrocarbons are derived from oxidation of unsaturated fatty acids in foods (Märk et al, 2006;Oomah & Liang, 2007). Trichloromethane (chloroform), produced on exposure to chlorinated organic compounds, is a natural compound in plants (Lovegren et al, 1979).…”
Section: Hydrocarbonsmentioning
confidence: 99%
“…Monitoring specific chemical reactions in coffee using on-line direct mass spectrometry has also been reported (Muller et al, 2006). Acrylamide formation has also been studied using on-line techniques Channell et al, 2008) as have the formation of food contaminants (furan and methyl furan; Mark et al, 2006) and aromas .…”
Section: Monitoring Flavour Generation On-linementioning
confidence: 99%
“…For acrylamide, it was found that gas-phase contents were directly related to amounts in the solid phase and a calibration curve could be constructed although it was temperature dependent . On-line mass spectrometry for following chemical reactions is a relatively new technique although there are some published examples in the literature on non-food applications (see for example Brum and Dell'Orco, 1998;Dell'Orco et al, 1999;Brum et al, 2001;Mark et al, 2006). It is a powerful tool for studying real foods as well as the dynamics of individual reaction steps in the Maillard reaction.…”
Section: Monitoring Flavour Generation On-linementioning
confidence: 99%